Apatite and titanite from the Karrat Group, Greenland; implications for charting the thermal evolution of crust from the U-Pb geochronology of common Pb bearing phases - Kirkland, Chris; Hollis, Julie; Danisik, Martin; Petersen, J.; Evans, Noreen; McDonald, B. (Elsevier BV, 2017)
Titanite and apatite have Pb closure temperatures of ~700 °C and 450–550 °C, respectively, allowing different points on a cooling trajectory to be determined. However, both phases typically accommodate moderate to significant quantities of common Pb. Understanding the thermal diffusivity of a specific isotopic system in different minerals along with their apparent U-Pb age allows modelling of regional cooling trends. Such cooling trends may provide key evidence for correct interpretation of the measured geochronometer. Specifically, thermal history reconstruction may address questions related to the interpretation of an isotopic date as the time of crystallization versus cooling, or alternatively, as a resetting age. In this work, a case study from metavolcanic rocks of the Karrat Group, West Greenland, is used to inform the U-Pb geochronology of common Pb bearing phases, thermal modelling, and also the regional geology. Magmatic apatite yields a reset U-Pb age of 1826 ± 9 Ma, whereas titanite yields a mean U-Pb age of 1768 ± 8 Ma. The apatite age is interpreted as the time of total resetting during a > 485 °C event. In contrast, the titanite age is interpreted as the time of metamorphic crystallization, consistent with its REE chemistry. Thermal modelling indicates this metamorphic event did not exceed 452 °C. The resetting of the U-Pb system in magmatic apatite is interpreted as a response to the collision between the Rae Craton and the Superior Craton during the Trans-Hudson Orogeny. However, subsequent metamorphic titanite growth is interpreted as distal evidence of an event shared with the Nagssugtoqidian Orogen. The modelled thermal history implies over 100 million years of communal tectonic history between the Nagssugtoqidian and Rinkian Orogens. Of great significance is the fact that both apatite and titanite show distinctly different common Pb compositions. Apatite retains common Pb with a composition similar to ancient common Pb, whereas titanite retains common Pb with a lower 207 Pb/ 206 Pb ratio implying it was influenced also by Pb from recrystallized precursor U bearing minerals. The common Pb signature in minerals may assist in interpretation of the growth mechanism of the dated phase.